SIKLUS KEHIDUPAN DALAM SENI LUKIS KUBISME - Zola Alfiandra, Yasrul Sami, S.Sn., M.Sn., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2018)
Aims to visualize the cycle of life as a disturbing thing in the family’s social through cubism painting.Creation of a work of art, need to make variety of preparations, such as making fforts to observation, information searching, appreciation, contemplation, xcavation of reference, and literacy related to the initial idea, as well as indirect material eepening around the environment in accordance with the problem.Some works of rt have been presented exclusively with titles namely, Space (Cause), hydration(Effect), fifteen roman, Audible, Irritation (Disturbance), Consciousness, ome, Wild, Position, and figure. This is the main point of the troubling things in the family.Kata Kunci: Siklus Kehidupan dalam Seni Lukis Kubisme